2021
DOI: 10.1111/dar.13227
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of alcohol policies in the Latin America and the Caribbean

Abstract: Introduction The aim of this paper is to describe the context of alcohol use and problems in Latin America and the Caribbean (LAC), the environmental context for alcohol‐related policy, drinking trends, harm and policy and to systematically review policies implemented to reduce alcohol‐related burden. Methods LAC‐based studies relating to the existence and effects of public health‐oriented alcohol policies are described. The review is informed by a literature search of alcohol policies in LAC in English and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…There are major human capital and economic windfalls awaiting governments that adopt nation-wide, best-practice alcohol interventions. Manifestly underutilised, independently and collectively, the full potential of these strategies has been scarcely realised, though they offer evidence-based solutions for high- and low-income countries alike [ 151 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are major human capital and economic windfalls awaiting governments that adopt nation-wide, best-practice alcohol interventions. Manifestly underutilised, independently and collectively, the full potential of these strategies has been scarcely realised, though they offer evidence-based solutions for high- and low-income countries alike [ 151 ].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of 100% alcohol-attributable deaths in the selected countries in the Americas occurred prematurely among those aged less than 60 years, which may have greatly impacted the economies and human capital of these countries. To prevent and reduce further harms from alcohol use in the Americas in the future, countries in that region should not only improve the quality of their alcohol-related data, but should also implement effective interventions and policies, such as the cost-effective strategies outlined in the World Health Organization's new technical package called 'SAFER' to reduce alcohol availability and consumption [18,53]. men for the Americas, from 2013 to 2015 inclusive.…”
Section: Discussionmentioning
confidence: 99%
“…The 100% alcohol-attributable deaths are estimated to represent fewer than 30.0% of all alcohol-attributable deaths in the Americas (based on [3,11]); however, they represent a unique category which is impacted greatly by heavy chronic drinking and HED [7]. Therefore, the burden of 100% alcohol-attributable deaths has unique policy implications for both general population interventions, including taxation/pricing increases and marketing and availability restrictions, and targeted interventions, including brief interventions [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…For example, a study in the United States showed that longer sales hours at the state/district level were associated with high-risk sexual behaviors [92], which are associated with HIV transmission. However, implementation of effective alcohol control policies such as the best buys is relatively low around the world, particularly in lower-and middle-income countries [206][207][208][209], many of which have the highest disease burden with respect to many communicable diseases [136]. Implementation and enforcement of effective alcohol control policies as a means of reducing the burden of communicable diseases is recommended.…”
Section: Alcohol Control Measuresmentioning
confidence: 99%